2016
DOI: 10.5897/ajb2015.15077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of boiling and oil or vinegar on pickled jurubeba (Solanum paniculatum L.) fruit

Abstract: Jurubeba fruit, raw and thermally processed for different periods of time, were preserved in soybean oil or vinegar and evaluated for physical characteristics, phytochemicals, antioxidant capacity and polyamines. The loss of green color in many vegetables after cooking is a frequent problem that affects the quality of pickled foods, and chlorophyll content is a relevant parameter to assess the quality. Data showed that a 20 min cooking treatment maintained the best fruit quality and no change in the chlorophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Similar observations were made in Solanum paniculatum fruit (29). On the other hand, the decreased amount of flavonoids in boiled A. auricula-judae and unpeeled potato suggest that they may either have been denatured or leaked into the boiling vessel.…”
Section: Discussionsupporting
confidence: 86%
“…Similar observations were made in Solanum paniculatum fruit (29). On the other hand, the decreased amount of flavonoids in boiled A. auricula-judae and unpeeled potato suggest that they may either have been denatured or leaked into the boiling vessel.…”
Section: Discussionsupporting
confidence: 86%
“…Means followed by the same lowercase letter in the column are not significantly different (P [ 0.05) of oxidation. In a previous study, we also observed a lower content of putrescine in jurubeba fruit preserved in vinegar (Silva et al 2016). It is well known that microbiological contamination is one of the main factors influencing the BAs levels in food, but the low pH induced by vinegar minimizes microbiological contamination.…”
Section: Samplesupporting
confidence: 58%
“…Before the thermal process, 5 kg of each sample set of fruits were cleaned with tap water and later immersed for 10 min in chlorinated water (containing 20 mg of free chlorine per liter). Thereafter, one portion was kept raw, and the other (500 g of each sample) was cooked for 20 min in a stainless steel pan containing 1 L of boiling water (Silva et al 2016). Samples were drained and cooled rapidly.…”
Section: Thermal Process and Pickling Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturity index: obtained by means of the relationship between soluble solids and titratable acidity contents. Flavonoids: determined according to the method described by Popova et al (2004) and adapted by Silva et al (2016). The extraction was carried out in acidified acetone (70%) and absorbance was measured at 425 nm in a spectrophotometer (BEL Photonics®, SP 2000 UV/VIS).…”
Section: Variables Evaluatedmentioning
confidence: 99%